Association between dietary carrot intake and breast cancer: A meta-analysis. Issue 37 (September 2018) - Chen, Haichao; Shao, Faming; Zhang, Fei; Miao, Qilong
Abstract: Background: We aimed to estimate the association between dietary carrot intake and risk of breast cancer by conducting a meta-analysis of epidemiologic studies. Methods: Relevant studies were identified by searching databases through September 2017. We included studies that reported risk estimates with 95% confidence intervals for the association between dietary carrot intake and breast cancer risk. Random-effects models were used to calculate the summary risk estimates. Publication bias was estimated using Begg's funnel plot and Egger's regression asymmetry test. Results: A total of 10 articles met the eligibility criteria and were included in the meta-analysis involving 13, 747 cases. The combined odds ratios (ORs) of breast cancer for the highest compared with the lowest dietary carrot intake was 0.79 (95% CI: 0.68, 0.90), and a significant heterogeneity was observed. In the subgroup analyses separated by study design, the inverse associations were more pronounced in the case–control studies than in the cohort studies, while the associations did not significantly differ by geographical region, study quality, exposure assessment. Omission of any single study had little effect on the combined risk estimate. Conclusion: The overall current literatures suggested that dietary carrot intake was associated with decreased risk of breast cancer.